COLLABORATIVE GOVERNANCE IN THE MANAGEMENT OF LIGHT RAIL TRANSIT (LRT) IN THE CITY OF PALEMBANG - M. Yoga Jusri Pratama; Alfitri; Abdul Nadjib; Raniasa Putra (RADJA PUBLIKA, 2026)
Study This aim For analyzing Collaborative Governance in management of Light Rail Transit (LRT) in Palembang City. The presence of LRT as transportation modern mass is expected capable reduce congestion, increasing mobility society, and create system transportation sustainable urban development. However, Thus, the management of the Palembang LRT is still face various challenges, such as low level occupation passengers, height cost operational, not yet optimally integration between fashion transportation, as well as weakness coordination between stakeholder interests. Research This use method study qualitative approach​ descriptive. Data collection techniques are carried out through observation, interviews, documentation, and studies literature. Research results show that Collaborative Governance in Palembang LRT management has not yet walk optimally. Coordination between government area, LRT operator, sector private sector and community Still face various obstacles, especially in aspect communication, integration service transportation, and participation society. In addition, sustainability LRT operations are still very dependent on subsidies government Because low income operational. Research This conclude that strengthening collaboration between stakeholders, increasing integration transportation, as well as involvement public in a way active become factor important in increase effectiveness and sustainability LRT management in Palembang City.